Thermal Finite-Element Model of Electric Machine Cooled by Spray - Christian Bergfried; Samaneh Abdi Qezeljeh; Ilia V. Roisman; Herbert De Gersem; Jeanette Hussong; Yvonne Späck-Leigsnering (Energies)
The demand for higher power density in electrical machines necessitates advanced cooling strategies. Spray cooling emerges as a promising and relatively straightforward technology, albeit involving complex physics. In this paper, a quasi-3D thermal finite-element model of stator winding is created by the extrusion of a 2D cross-sectional finite-element model along the winding direction. The cooling effects of the spray impact are simulated as a heat flux that uses an impedance boundary condition at the surface of the winding overhang. The results confirm the advantageous performance of spray cooling, indicating that it may enable a tenfold increase in power density compared to standard air- or water-cooled machines.